Cochrane Database of Systematic Reviews 2013
DOI: 10.1002/14651858.cd008216.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Autologous hematopoietic stem cell transplantation following high dose chemotherapy for non-rhabdomyosarcoma soft tissue sarcomas

Abstract: Autologous hematopoietic stem cell transplantation following high dose chemotherapy for non-rhabdomyosarcoma soft tissue sarcomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 209 publications
(1 reference statement)
0
15
0
Order By: Relevance
“…Example 1: Non-rhabdomyosarcoma soft tissue sarcomas. 22 This systematic review evaluated autologous haematopoietic stem cell transplantation (autoHSCT) following high-dose chemotherapy (HDCT) versus standard-dose chemotherapy (SDCT) in patients with non-rhabdomyosarcoma soft tissue sarcomas (NRSTS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Example 1: Non-rhabdomyosarcoma soft tissue sarcomas. 22 This systematic review evaluated autologous haematopoietic stem cell transplantation (autoHSCT) following high-dose chemotherapy (HDCT) versus standard-dose chemotherapy (SDCT) in patients with non-rhabdomyosarcoma soft tissue sarcomas (NRSTS).…”
Section: Resultsmentioning
confidence: 99%
“…In a planned update 2 years later, we were able to identify a single RCT. 22 Using different study types provided the advantage to report estimates of overall survival in the first version when RCTs were lacking. The advantage affected also the update version because the reporting of adverse events exceeded the scope of a single RCT considerably.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a study conducted by Zhang et al analyzed a cohort of 48 patients with DSRCT and found median overall survival of 24 months; the variables associated with improved OS included “surgery, effective debulking surgery, chemotherapy, and any two or more combined therapeutics” ( p < 0.05). There was also a Cochrane Review that examined SCT in nonrhabdomyosarcoma STS, within which 27 patients carried a diagnosis of DSRCT [ 9 , 23 ]. The graph of OS of the 27 patients with DSRCT appeared similar to the graph of the 80 total patients, but there was no direct statistical comparison.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Despite treatment, survival prognosis remains poor ( Table 1 ), with most patients experiencing resistant and recurrent disease before end of life. 14,15 The data on use of HIPEC in DSRCT is scarce, however, Hayes-Jordan et al showed that HIPEC has improve survival outcomes with patients receiving neoadjuvant chemotherapy followed by cytoreductive surgery and HIPEC having a 3 year survival of 71% compared to 26% ( p = 0.021) in patients who did not receive surgery or HIPEC. 1 Our follow up has been shorter and hence we were unable to make a direct comparison in terms of survival.…”
Section: Discussionmentioning
confidence: 99%